Relationship of Change in Cervical Curvature after Laminectomy with Lateral Mass Screw Fixation to Spinal Cord Shift and Clinical Efficacy - Hou, Shu-bing; Sun, Xian-ze; Liu, Feng-yu; Gong, Rui; Zhao, Zheng-qi; Lu, Kuan; Liu, Yan-bing (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Although laminectomy with lateral mass screw fixation (LCSF) is an effective surgical treatment for cervical spondylotic myelopathy (CSM), loss of cervical curvature may result. This study aimed to investigate the effect of cervical curvature on spinal cord drift distance and clinical efficacy.Patients and Methods We retrospectively analyzed 78 consecutive CSM patients with normal cervical curvature who underwent LCSF. Cervical curvature was measured according to Borden's method 6 months after surgery. Study patients were divided into two groups: group A, reduced cervical curvature (cervical lordosis depth 0–7mm; n = 42); and group B, normal cervical curvature (cervical lordosis depth 7–17mm; n = 36). Spinal cord drift distance, laminectomy width, neurologic functional recovery, axial symptom (AS) severity, and incidence of C5 palsy were measured and compared.Results Cervical lordosis depth was 5.1 ± 1.2 mm in group A and 12.3 ± 2.4 mm in group B (p < 0.05). Laminectomy width was 21.5 ± 2.6 mm in group A and 21.9 ± 2.8 mm in group B (p > 0.05). Spinal cord drift distance was significantly shorter in group A (1.9 ± 0.4 vs. 2.6 ± 0.7 mm; p < 0.05). The Japanese Orthopaedic Association (JOA) score significantly increased after surgery in both groups (p < 0.05). Neurologic recovery rate did not differ between the two groups (61.5 vs. 62.7%; p > 0.05). AS severity was significantly higher in group A (p < 0.05). C5 palsy occurred in three group A patients (7.1%) and four group B patients (11.1%), but the difference was not significant (p > 0.05).Conclusion After LCSF, 53.8% of the patients developed loss of cervical curvature. A smaller cervical curvature resulted in a shorter spinal cord drift distance. Loss of cervical curvature was related to AS severity but not improvement of neurologic function or incidence of C5 palsy.
Keywords: laminectomy; cervical spondylotic myelopathy; cervical curvature; axial symptoms; C5 palsy